Quality assessment of wine from purple rice (Oryza sativa var. tapul) - Cervantes, Carmela Mae Masnaño (2009.)
Production of wine using purple glutinous rice, tapul (Oryza sativa var. tapul) as the main substrate was conducted in a factorial experiment in RCBD.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Glutinous rice; Wine